LEGALITY AND MANAGEMENT ENVIRONMENTAL MONITORING OF INDEPENDENT PALM OIL FARMER’S TOWARD ENVIRONMENT BENEFITS - Artono, Artono; Nurliza, Nurliza; Maswadi, Maswadi (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACTEnvironmental benefits as a reference in measuring the physical condition and quality of environment as a result of palm oil farmer’s measured through legality and management environment monitoring. Palm oil plantations are claimed to be one of the causes of environmental degradation. These problems trigger the need to research on palm oil farmer’s to find out the conditions in the field related to the influence of self-help palm oil farmer’s on the environment. This research aims to analyze the influence of legality and management environment monitoring of palm oil farmer’s on environmental benefits, in 150 respondents selected purposively. Data analysis using by Structural Equation Modelling (SEM). The results of the research prove that the management environment monitoring of the plantation environment has a positive effect on environmental benefits, with the most affected indicators being fire prevention and control. This can increase independent palm oil farmer’s to maintain the sustainability of environmental benefits. Keywords: Environment Benefits, Legality, Management Environmental Monitoring, Structural Equation Modelling (SEM).